Linear accelerators for radiation sterilization developed in NPK LUTS NIIEFA - Vorogushin, M.F.; Gavrish, Yu.N.; Demsky, M.I.; Maksimov, V.M. (Вопросы атомной науки и техники, 2004)
NPK LUTS NIIEFA has been developing linear accelerators for industrial applications during about 30 years. More than 150 linear accelerators for different applications have been manufactured by this company and installed in different regions of Russia and abroad: in Poland, Hungary, Germany, France, China and India. The linear accelerators for radiation sterilization developed in NPK LUTS NIIEFA are reviewed.